2021
DOI: 10.1002/jgc4.1419
|View full text |Cite
|
Sign up to set email alerts
|

Exploring racial and ethnic minority individuals’ journey to becoming genetic counselors: Mapping paths to diversifying the genetic counseling profession

Abstract: According to the National Society of Genetic Counselors (NSGC), 90% of professionals practicing in the field of genetic counseling in the United States (U.S.) identify as non-Hispanic White (NSGC, 2019b). In contrast, approximately 40% of the U.S. population is comprised of people from diverse racial/ethnic backgrounds, including those who identify as Black or African American, Hispanic or Latinx, American Indian, Asian, Native Hawaiian or Alaskan, or two or more races (U.S. Census Bureau, 2018). This lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 24 publications
6
34
0
Order By: Relevance
“…Among participants who reported little or no knowledge of genetic counseling, the higher representation of BIPOC‐identifying teachers compared to white‐identifying teachers mirrors existing findings of decreased awareness of genetic counseling among BIPOC students, teachers, and US adults (Alvarado‐Wing et al, 2021; Gerard et al, 2019; Oh & Lewis, 2005; Pasca et al, 2022; Schneider et al, 2009; Schoonveld et al, 2007; Urli et al, 2020). Similar to previous findings that BIPOC students have high interest in genetic counseling once learning about it (Gerard et al, 2019; Oh & Lewis, 2005; Schneider et al, 2009; Urli et al, 2020), teachers in this study who reported higher levels of knowledge about genetic counseling, regardless of their self‐identified RE identity, perceived the presentation of genetic counseling as more important and presented it more frequently than teachers with little to no knowledge of genetic counseling.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Among participants who reported little or no knowledge of genetic counseling, the higher representation of BIPOC‐identifying teachers compared to white‐identifying teachers mirrors existing findings of decreased awareness of genetic counseling among BIPOC students, teachers, and US adults (Alvarado‐Wing et al, 2021; Gerard et al, 2019; Oh & Lewis, 2005; Pasca et al, 2022; Schneider et al, 2009; Schoonveld et al, 2007; Urli et al, 2020). Similar to previous findings that BIPOC students have high interest in genetic counseling once learning about it (Gerard et al, 2019; Oh & Lewis, 2005; Schneider et al, 2009; Urli et al, 2020), teachers in this study who reported higher levels of knowledge about genetic counseling, regardless of their self‐identified RE identity, perceived the presentation of genetic counseling as more important and presented it more frequently than teachers with little to no knowledge of genetic counseling.…”
Section: Discussionsupporting
confidence: 58%
“…Multiple studies have shown that BIPOC high school and college students have lower awareness of genetic counseling than their white peers, despite having high interest once exposed to the profession (Gerard et al, 2019; Oh & Lewis, 2005; Schneider et al, 2009; Urli et al, 2020). In addition, genetic counselors and genetic counseling students of underrepresented identities and communities have noted lack of early introduction to the career as a barrier to entering the field (Alvarado‐Wing et al, 2021; Schoonveld et al, 2007). As such, one frequently recommended method for increasing diversity in genetic counseling and other healthcare professions is introducing these career options during high school (Gerard et al, 2019; Mittman & Downs, 2008; Oh & Lewis, 2005; Owens et al, 2009; Schneider et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While this is a necessary initiative, it will likely take several years before the demand is met, if at all. Additional systemic issues in the awareness of the profession and the application process must be addressed to support the diversification of the profession (Alvarado‐Wing et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While several participants expressed satisfaction with their current supervision practices, they also expressed a desire for additional training in how to approach race/ethnicity in supervision. A suggested starting point is additional training for program faculty and supervisors in cultural biases and assumptions, as well as cultural humility (a term that has replaced ‘cultural competence’ to describe a more lifelong process and commitment to cultural self‐awareness and cultural sensitive practice) (Alvarado‐Wing et al., 2021; Carmichael et al., 2021; Greene‐Moton & Minkler, 2020). Before developing training and practice recommendations, however, more discussion with genetic counselor supervisors is needed to understand the discordance between satisfaction with current practices and the desire for additional training, as well as evidence‐based strategies to improve the experience of racial and ethnic minorities in clinical experiences (Alvarado‐Wing et al., 2021).…”
Section: Discussionmentioning
confidence: 99%